2011
DOI: 10.1021/mp200209j
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystals of Quercetin with Improved Solubility and Oral Bioavailability

Abstract: Flavonoids have been studied extensively due to the observation that diets rich in these compounds are associated with lower incidences of many diseases. One of the most studied flavonoids, quercetin, is also the most abundant of these compounds in the plant kingdom. Numerous therapeutic bioactivities have been identified in vitro. However, its in vivo efficacy in pure form is limited by poor bioavailability, primarily due to its low solubility and consequent low absorption in the gut. Cocrystallization has ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
283
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(296 citation statements)
references
References 48 publications
11
283
1
1
Order By: Relevance
“…8,9 It has been demonstrated that the formation of co-crystals can improve several properties of APIs, such as bioavailability, stability, hygroscopic properties, compressibility, and flowability. 5 Smith et al 10 successfully produced the 1:1 molar ratio cocrystal of Q-caffeine. Moreover, the co-crystals enhanced solubility up to 14-fold and up to 10-fold compared with those of Q and Q dihydrate, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 It has been demonstrated that the formation of co-crystals can improve several properties of APIs, such as bioavailability, stability, hygroscopic properties, compressibility, and flowability. 5 Smith et al 10 successfully produced the 1:1 molar ratio cocrystal of Q-caffeine. Moreover, the co-crystals enhanced solubility up to 14-fold and up to 10-fold compared with those of Q and Q dihydrate, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, agents that confer cardioprotection at the onset of reperfusion after myocardial ischemia provide a promising approach to attenuate myocardial I/R injury. Que is a member of the flavonoid family and is widely present in the plant kingdom (7). Que manifests a wide range of beneficial biological activites and can mediate cardioprotective effects (7,23).…”
Section: Discussionmentioning
confidence: 99%
“…Que is a member of the flavonoid family and is widely present in the plant kingdom (7). Que manifests a wide range of beneficial biological activites and can mediate cardioprotective effects (7,23). For example, an increased intake of Que has been suggested to reduce risk of cardiovascular diseases (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the synthesis of four types of co-crystals led to an improvement in physicochemical and pharmacokinetic characteristics in comparison with free quercetin. 53 Other reports have described the use of cellulose nanocrystals (CNCs) as viral inhibitors. The first approach was carried out with unmodified CNCs derived from tunicates in a single model, and a decrease in phage infection of host E. coli was observed.…”
Section: Antiviral Drugsmentioning
confidence: 99%